Dissolution behavior of a novel composite fiber made from blast furnace slag. (10th May 2019) - Li, Xiaoguang; Liu, Jinjin; Qin, Jinyi; Liu, Yunxiao; Qu, Yaan; Zhang, Rui
Graphical abstract: Highlights: The water-resistant of composite slag fiber can be improved by adjusting the AC value. Lower AC, the stability of the Al-O network structure was prone to be damaged. The coverage and shedding of Ca-rich layer affected the dissolution behavior. Abstract: A novel composite fiber was made from chemically modified blast furnace slag, it has been widely used in construction field of china, but the related dissolution behavior was unclear. Specimens of the fibers with different acidity coefficient (AC) by adding basalt, ranging from 0.93 to 1.19, were immersed into deionized water for 180 days. The surface morphology was studied by scanning electron microscopy (SEM). The element concentration on the surface and in aqueous phase was determined by Energy dispersive X-ray spectroscopy (EDS) and inductively coupled plasma spectroscopy (ICP), respectively. The results showed that the fiber surface newly formed calcite crystal when the AC was lower than 1.03. Portion of Al element was converted from four coordination forms to a combination of six coordinations. In the leaching experiment, as the AC increased, the concentration of Ca 2+ in the aqueous phase decreased significantly, and the corresponding Mg 2+ release increased slightly. As a result, the dissolution behavior was hindered by adjusting AC value and it was helpful to further improve the water-resistant quality of new slag fiber.